Analisis Gaya Belajar Siswa Sekolah Menengah Atas (SMA) Muhammadiyah 3 Jember - Mahardika Fitra Setiawan; Anggraeni Swastika Sari; Festa Yumpi Rahmanawati (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2025)
Learning styles refer to the ways students concentrate, process, absorb, and retain new and complex information. The VARK learning model encompasses four primary modalities: Visual, Auditory, Read, and Kinesthetic. This study aims to describe the learning styles of students at SMA Muhammadiyah 3 Jember. A descriptive quantitative method was used with a population of 252 students and a sample of 146 respondents selected through purposive random sampling. The learning style scale was adapted from an existing instrument. Data were analyzed using descriptive statistical tests with the Jamovi for Windows application. The results show that students generally tend to have a visual learning style, indicating a preference for media such as videos or images. Based on gender, male students tend to prefer auditory learning, while female students are more visually oriented. Based on grade level, 10th-grade students lean toward a reading learning style, while 11th-grade students favor auditory learning.